Optimized Design of Distributed Generalized Reed-Solomon Coded Generalized Spatial Modulation - L. Zhao, C.; F. Yang, F.; J. Xu, H. (Radioengineering, 2025)
To meet the need of modern society for more reliable and efficient communications, this paper applies the generalized spatial modulation (GSM) technique in the distributed generalized Reed-Solomon (GRS) coding to propose a novel distributed GRS coded GSM (DGRSC-GSM) system. In the proposed system, the relay uses the concept of information symbol selection. For different information symbol selections, the destination generates different equivalent linear block codes. To achieve the optimized system design, the optimal information symbol selection (OISS) algorithm by complete search in the relay is proposed to make the destination obtain the best code having the optimal weight distribution. When the GRS codes at the source and relay have large information lengths, the OISS algorithm possesses high complexity. Thus, a low-complexity optimized information symbol selection (LC-OISS) algorithm by incomplete search is put forward. For realizing the effective retrieve of the overall source information, a new joint decoding algorithm in the destination is designed. The results show the superior performance of the proposed DGRSC-GSM system under the OISS and LC-OISS algorithms over that under the random information symbol selection algorithm. Also, the proposed system outperforms the non-cooperative system by 2.6 dB and exhibits more than 2 dB improvement over existing systems.